Alkyl Carbagermatrane Enabled Synthesis of Seven-Membered Carbocycle-Fused Aromatics through Catellani Strategy - Xie, Xiu-Ying; Jiang, Wei-Tao; Xiao, Bin (Synthesis, 2021)
Synthesis of seven-membered carbocycle-fused aromatics was realized by Catellani reaction using terminally brominated alkyl carbagermatranes through intermolecular cyclization manner. Various functional groups were well tolerated, and this transformation was also expanded to the synthesis of carbocycles of other size. The utility of this method was demonstrated by modification of natural product derivatives and synthesis of bioactive molecules.
Keywords: Catellani reaction; alkyl carbagermatranes; seven-membered carbocycles; cyclization; organogermanium